The Future of Cultural Heritage Conservation amid Urbanization in Asia: Constraints and Prospects - Horayangkura, Vimolsiddhi (Journal of Architectural/Planning Research and Studies (JARS), 2005)
Given the national commitments and the international criteria for nomination of cultural properties and cultural landscapes to be inscribed on the World Cultural Heritage List, and various threats from multiple external forces as well as intrinsic constraints among Asian countries, this study then attempts to investigate the significant variables, their applicabilities to and impacts on conservation implementation and potential performances. Through reviewing conservation experiences in Asian regions, critical constraints and prospects in terms of positive approaches are explored together with demonstrating distinctive examples of World Cultural Heritage and Asia-Pacific’s best practices in conservation. The outputs of these investigations set up the conceptual framework of challenge for escalating the conservation movements in Thailand.